Indolent systemic mastocytosis in a patient with ileocolitis - Chrysakopoulos, Georgios (Hellenic Society of Gastroenterology, 2014)
Systemic mastocytosis is a clonal disorder of the mast cell and its progenitor cell. It is a rare disorder with unknown incidence in Greece, with an estimate of 2 cases per year in Great Britain. We present a case of an asymptomatic, 72-year-old man who was found to have ileocolitis on endoscopy. Histology revealed mast cells in lamina propria >15 HPF and biochemistry showed high levels of serum total tryptase. Molecular testing was positive for the mutation Asp816Val in exon 17 of c-kit gene. The patient met one major and two minor criteria for the diagnosis of systemic indolent mastocytosis (according to WHO classification). He has been treated prophylactically with H(1)- and H(2)-histamine receptor antagonists and remains asymptomatic.